Comorbidities Associated with Severity of Atopic Dermatitis in Young Adult Males: A National Cohort Study - Wai Leong Kok; Yik Weng Yew; Tien Guan Thng (Medical Journals Sweden, 2019)
Atopic dermatitis (AD) is a systemic inflammatory disorder. However, the relationship between severity of AD and metabolic and atopic conditions is not well studied. The aim of this study was to elucidate the relationship between severity of AD and comorbidities, such as metabolic conditions (increased body mass index, hypertension, hyperlipidaemia, and type II diabetes mellitus) and other atopic manifestations (allergic rhinitis, asthma and food allergies). A retrospective population-based national study of a cohort of young adult males conscripted into military service in Singapore over a 5-year period was performed, utilizing military electronic medical records. A dose-dependent effect was found between the association of comorbidities and severity of AD. Metabolic and atopic conditions were significantly correlated with having moderate-to-severe AD. An association of metabolic and atopic conditions with severity of adult AD was found, which suggests that chronic severe AD may result in increased disease burden and morbidity.